2021
DOI: 10.1007/s10654-021-00766-0
|View full text |Cite
|
Sign up to set email alerts
|

The impact of non-pharmaceutical interventions on COVID-19 epidemic growth in the 37 OECD member states

Abstract: We estimated the impact of a comprehensive set of non-pharmeceutical interventions on the COVID-19 epidemic growth rate across the 37 member states of the Organisation for Economic Co-operation and Development during the early phase of the COVID-19 pandemic and between October and December 2020. For this task, we conducted a data-driven, longitudinal analysis using a multilevel modelling approach with both maximum likelihood and Bayesian estimation. We found that during the early phase of the epidemic: impleme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
67
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(69 citation statements)
references
References 29 publications
2
67
0
Order By: Relevance
“…The impact of other non-pharmaceutical public health measures, including workplace closings, voluntary quarantine compliance, shelter-in-place, and masking mandates have been considered and compared in prior work [ 7 , 9 , 20 , 31 , 53 – 56 ]. Some studies found that the public health effects of school closures are similar to that of workplace closures [ 20 , 53 , 54 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The impact of other non-pharmaceutical public health measures, including workplace closings, voluntary quarantine compliance, shelter-in-place, and masking mandates have been considered and compared in prior work [ 7 , 9 , 20 , 31 , 53 – 56 ]. Some studies found that the public health effects of school closures are similar to that of workplace closures [ 20 , 53 , 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…The impact of other non-pharmaceutical public health measures, including workplace closings, voluntary quarantine compliance, shelter-in-place, and masking mandates have been considered and compared in prior work [ 7 , 9 , 20 , 31 , 53 – 56 ]. Some studies found that the public health effects of school closures are similar to that of workplace closures [ 20 , 53 , 54 ]. Our study focused on the impact of various school reopening scenarios to provide policy suggestions to decision-makers amid an ongoing pandemic or epidemic, in the presence of other non-pharmaceutical interventions.…”
Section: Discussionmentioning
confidence: 99%
“…Aleta et al show that travel restrictions are likely to be effective measures only in the short term and may be less effective at a later stage and for the elimination of the infection (15,60). In order to have a better control of COVID-19 pandemic, other preventive and control measures such as promotion of the use of face masks, regular handwashing, school closures, and suspension of large public get-togethers should also be place (61). Other measures such as active surveillance and self-isolation of infected persons and their contacts should also be implemented (45).…”
Section: Discussionmentioning
confidence: 99%
“…However, these designs are limited in capturing herd immunity (indirect effect) and population-level effectiveness (overall effect of a vaccination program in the population) [ 12 , 13 , 14 ]. Furthermore, these designs were unable to examine the population-level outcomes of mass vaccination (e.g., the growth rate of infection cases [ 15 , 16 , 17 , 18 ], the number of cases averted [ 19 ]), which have important public health implications and provide evidence for policymaking. Some methods have been adopted to study the population-level effect (overall effect) of the COVID-19 vaccines, most of which are mathematical models.…”
Section: Introductionmentioning
confidence: 99%